Real-time mixed reality teleconsultation for intensive care units in pandemic situations - Roth, Daniel; Yu, Kevin; Pankratz, Frieder; Gorbachev, Gleb; Keller, Andreas; Lazarovici, Marc; Wilhelm, Dirk; Weidert, Simon; Navab, Nassir; Eck, Ulrich (Proceedings - 2021 IEEE Conference on Virtual Reality and 3D User Interfaces Abstracts and Workshops, VRW 2021, 2021)
Intensive care units (ICUs) that host patients infected by the SARS-CoV-2 Coronavirus are separated from other care units. In regular ICU ward rounds, a number of experts from different medical areas and expertise are present to discuss the situation and care of the patient. However, this procedure is contrasting COVID-19 measures such as reduced contact and personnel traffic. In this project, we demonstrate a system for mixed reality (MR) teleconsultation to support ICU wards (ARTEKMED). Through ARTEKMED, remote experts can join a local 3D reconstructed ICU visit in virtual reality (VR) and support local experts that are equipped with an augmented reality (AR) system. Our goal is to reduce personnel traffic and in turn the risk of an infection spread.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Human-centered computing; Virtual reality; Visualization